"Cast back into the dark ages of medicine"? The challenge of antimicrobial resistance - Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2015)
Antimicrobial resistance (AMR) is currently the focus of much media attention and policy discussion. A historical perspective on AMR suggests that although the challenge of AMR is real, the doomsday tone of most commentary is unwarranted. That is partly because most of the gains in life expectancy now deemed under threat preceded the antibiotics revolution. A combination of public health measures, rising living standards, and new medical knowledge all played their part in this. Even if AMR increases, the continuing effect of these factors and of new public health measures can limit the negative consequences. Moreover, recent developments suggest that the supply pipeline of new drugs is not quite as dry as usually claimed. The problem for now is not MRSA or malaria but carbapenem-resistant gram-negative bacteria, which pose an urgent threat and on which public funding for research on effective new therapies should concentrate.
Keywords: I; N; 330; infectious disease; health; antimicrobial resistance; economic history